Evaluación de la crioconservación de ovocitos en cuyes (cavia porcellus) en el laboratorio de biotecnología de la reproducción de la carrera de medicina veterinaria de la Universidad Técnica de Cotopaxi - Naranjo Zapata, Diana Maribel (2014)
The present research was carried out in the Laboratory of Biotechnology of the Reproduction of the Cotopaxi Technical University carrer in Veterinary Medicine. There were used of second birth 20 guinea pigs females , which were sacrificed to obtain 40 ovaries , which were collected in sterile containers with sodium chloride 0.9% allowing fresh maintenance of ovaries and avoiding causing damage at the level of ovarian structures. The main objective of this research was to evaluate the cryopreservation of oocytes using slicing technique (cut of ovaries), which consists in dorny fine-cut and separated on the surface and inside of the ovary to extract fluid follicular, after put it in a petri dish, through of the observation by microscopy, could observed the morphological characteristics of oocytes, with this work determined the quality parameters and after freezing and the maturity of the oocytes....